115 Evaluation of the use of a patient held record in specialist palliative care. Issue Volume 8: Issue (2018)Supplement 1 (1st March 2018) - White, Clare; Sproule, Jenny; Brogan, Paula; Watson, Max
Abstract : Introduction: The Royal College of GPs in Northern Ireland created a Patient Held Record (PHR) for patients with progressive, life-limiting illness and their families. This study evaluates its usefulness in the specialist palliative care context. Methods: A prospective longitudinal cohort study through a hospice community service. Patients were given questionnaires with the passport and after 4–6 weeks. Hospice Healthcare Professionals (HCPs) completed a questionnaire and focus group after 8 months. Results: From September 2016–June 2017, 550 patients were screened, 347 (63.1%) were offered a passport and 259 accepted it (74.6% of those offered). 238 patients accepted a research pack, with 105 returning questionnaire 1 (44.1% response rate), and 26 returning questionnaire 2 (24.8% of initial respondents). Questionnaire 1 (patients) – 40% found it difficult or burdensome repeating information to HCPs, and almost 70% were interested in a PHR to reduce repeating information. Questionnaire 2 (patients)- 74% found it the passport easy to use, but only a few actually used it regularly. Some felt the passport helped conversations with family and HCPs about day-to-day and future care. Over 60% stated the PHR was 'very' or 'quite' useful', and would recommend it to others. Questionnaire and focus group with HCPs indicated it was mainly patients and relatives who used the passport, not non-palliative HCPs. Half felt the passport was initially well received, but only 4 (22%) felt it was used regularly by patients or their families. More found it useful to talk about facilitation discussion about future care compared with day-to-day care. Conclusions: While initial uptake of the passport was high, use appeared low. This evaluation does not support widespread use of a PHR in palliative care, but it may be helpful to individuals, especially earlier in their disease trajectory.